Penggunaan Ifdil perceptual light technique (IPLT) dengan ayat-ayat Al-quran - Miftahhuddin, Miftahuddin; Suhaimi Suhaimi; Cherly Nadifa; M. Fahli Zatrahadi; Suhertina Suhertina; Rahmad Rahmad; Istiqomah Istiqomah; Ifdil Ifdil (Jurnal Konseling dan Pendidikan, 2024)
This study aims to evaluate the effectiveness of the Ifdil Perceptual Light Technique (IPLT) combined with Qur'anic verses in enhancing clients' mental and spiritual balance. The research employs a case study approach with qualitative methods, involving in-depth interviews and observations of six participants, consisting of two therapy experts and four clients from Padang and Pekanbaru. Data analysis was conducted using NVivo software to identify relevant key themes. The study results revealed seven main themes, including the integration of spirituality and IPLT technology, the role of sensory elements in therapy, client responses to the therapy, success in mental and spiritual recovery, challenges in implementation, personalized therapy based on client needs, and perspectives on the future of holistic therapy. The key findings indicate that integrating IPLT with Qur'anic verses can help reduce anxiety levels, enhance spiritual connection, and create a deeper therapeutic experience. However, the study also highlights challenges in balancing technological and spiritual elements, as well as the importance of personalizing sensory elements such as light intensity and sound for each client. The implications of this study include the development of technology-based therapies tailored to clients' spiritual values, as well as recommendations for counseling services to create more holistic and inclusive approaches. These findings are particularly relevant for communities with strong cultural and religious backgrounds, such as those in Padang and Pekanbaru.